Mengembangkan Karakter Islami pada Anak Usia Dini melalui Metode Storytelling Visual di PAUD Plamboyan - Sulaeman, Devi; Daryana, Andepi; Hartiani, Enih; Fatah, Abdul; Waryani, Waryani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Islamic character education in early childhood has an important role in shaping children's morals and personality in accordance with Islamic values. This service activity aims to develop Islamic character in early childhood through the visual storytelling method at PAUD Plamboyan, West Karawang District. The method used is the Asset-Based Community Development (ABCD) approach, which emphasizes the use of local assets and active community participation in every stage of activities. This program includes storytelling skills training for educators, making Islamic visual props, as well as regular storytelling sessions involving children and parents. The results of the activities show an increase in understanding and internalization of Islamic values in children, such as honesty, discipline and caring, which is reflected in changes in their daily behavior. Apart from that, a new institution was formed in the community, namely a commitment from the school and parents to continue the storytelling method independently. The implication of this activity is increasing community awareness of the importance of collaborative Islamic character education between schools and families. The participation of educators as local leaders in this program also strengthens the sustainability and future development of the program. It is hoped that this activity can become a model for other institutions in implementing Islamic character education through innovative and participatory methods.